Análisis de la tendencia del crimen violento en la Zona Metropolitana del Valle de México - Peña González, Rodrigo (El Colegio de México A.C., 2024)
Based on a spatial and temporal analysis, this article aims to study the trend of violent crime in the Metropolitan Zone of the Valley of Mexico (ZMVM). To that end, rates of three violent crimes that function as analysis variables are mapped and studied: homicides (in general and committed with firearms), intentional injuries, and extortion. The main finding is that the criminal trend of ZMVM during the period studied has a considerable concentration around the border dividing Mexico City and the State of Mexico. Also, the data reveals secondary findings over three topics: the ZMVM during the war on drugs, the relation between metropolitan routes and illegal markets, as well as the relationship between violent crime and the recently inaugurated Felipe Ángeles International Airport. The conclusions document the relevance of the border areas in the general trend of violent crime in the ZMVM as well as the relevance of promoting a metropolitan vision of security across this space.